Europe at the crossroads: Constitution, enlargement and the future of European Union - Siriški Sofija (Međunarodni Problemi)
Following the largest enlargement of the EU from 15 to 25 Member States many people are asking the question: where does Europe end? The Union has already made political commitments to additional EU members: Romania, Bulgaria, Turkey, Croatia and the other Balkan countries and in spite of the European Neighbourhood Policy further thinking of the EU enlargement also includes Ukraine and Moldova. But the French and Dutch rejection of the constitutional treaty has made the future EU enlargement uncertain and the EU adopted a new comprehensive enlargement strategy based on consolidation of the EU.